The dragon takes a wife. - Myers, Walter Dean, 1937-; Grifalconi, Ann (Indianapolis, Bobbs-Merrill, 1972)
Unable to fight a knight and thus win a wife, Harry the dragon seeks help from an unconventional fairy.
K-3
K-3
710
Keywords: Fairy tales